2022
DOI: 10.3390/bioengineering9120762
|View full text |Cite
|
Sign up to set email alerts
|

Sensors and Techniques for On-Line Determination of Cell Viability in Bioprocess Monitoring

Abstract: In recent years, the bioprocessing industry has experienced significant growth and is increasingly emerging as an important economic sector. Here, efficient process management and constant control of cellular growth are essential. Good product quality and yield can only be guaranteed with high cell density and high viability. Whereas the on-line measurement of physical and chemical process parameters has been common practice for many years, the on-line determination of viability remains a challenge and few com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 139 publications
0
6
0
Order By: Relevance
“…The study explored the fermentation of biosurfactants by B. licheniformis and discovered a good correlation between the conductivity and primary fermentation products and between permittivity and the optical density of the fermentation broth. Such in-line real-time and continuous measurements support a better understanding of biosurfactant formation and reach higher productivity via cutting fermentations in optimal time [ 34 , 35 ]. The comparison of the tested three potential bio-fungicide-producing bacteria from fermentation revealed that the fastest cell growth could be reached by B. licheniformis with the highest biosurfactant amount resulting in the highest productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The study explored the fermentation of biosurfactants by B. licheniformis and discovered a good correlation between the conductivity and primary fermentation products and between permittivity and the optical density of the fermentation broth. Such in-line real-time and continuous measurements support a better understanding of biosurfactant formation and reach higher productivity via cutting fermentations in optimal time [ 34 , 35 ]. The comparison of the tested three potential bio-fungicide-producing bacteria from fermentation revealed that the fastest cell growth could be reached by B. licheniformis with the highest biosurfactant amount resulting in the highest productivity.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Acquiring a broader UV-VIS spectrum for each sample and coupling the analytical method with chemometric techniques allows one to create a rapid method for extracting biological and chemical information from the system. 21,22 Pre-processing of the spectra and the utilization of multivariate statistical analysis can provide qualitative and quantitative data about the biological systems and rapidly show differences between samples that single wavelength (univariate) analysis cannot. 23 Furthermore, the incorporation of machine learning methods or algorithms can also provide the potential to solve complex classification, regression, and outlier detection issues by performing optimal data transformations that determine boundaries between data points based on predefined spectra pertaining to the microbe/matrix/antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Current process parameters continuously monitored in cell manufacturing are limited to physical parameters such as temperature, pH, and dissolved oxygen concentration within the culture media. [10][11][12][13] Although these parameters can be used to maintain a healthy growth environment, these measurements do not accurately indicate the growth progression of cells. Monitoring cell proliferation directly would inform feeding, stimulation, and harvest decision time points.…”
Section: Introductionmentioning
confidence: 99%